2018
DOI: 10.3390/nano8060396
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Gold Nanoparticles Ameliorate Retinoic Acid-Induced Cell Death and Induce Differentiation in F9 Teratocarcinoma Stem Cells

Abstract: The unique properties of gold nanoparticles (AuNPs) have attracted much interest for a range of applications, including biomedical applications in the cosmetic industry. The current study assessed the anti-oxidative effect of AuNPs against retinoic acid (RA)-induced loss of cell viability; cell proliferation; expression of oxidative and anti-oxidative stress markers, pro- and anti-apoptotic genes, and differentiation markers; and mitochondrial dysfunction in F9 teratocarcinoma stem cells. AuNPs were prepared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 93 publications
0
16
0
Order By: Relevance
“…Furthermore, the over-expression of ATF6 increases the expression of CHOP, and JNK/NF-κB was also involved in ERS-induced cell apoptosis, which supports that ERS activates mitochondrion-mediated apoptosis [107]. RA was also reported to significantly activate the mRNA expression of p53, p21, Bax, Bak, caspase-3, and caspase-9, and decrease the expression of Bcl-2 and Bcl-Xl in F9 teratocarcinoma stem cells [66]. In this study, the combination of the two agents resulted in a more effective and efficient induction of programmed cell death in SH-SY5Y cells.…”
Section: Ptnps and Ra Induce Ers And Apoptosismentioning
confidence: 57%
See 1 more Smart Citation
“…Furthermore, the over-expression of ATF6 increases the expression of CHOP, and JNK/NF-κB was also involved in ERS-induced cell apoptosis, which supports that ERS activates mitochondrion-mediated apoptosis [107]. RA was also reported to significantly activate the mRNA expression of p53, p21, Bax, Bak, caspase-3, and caspase-9, and decrease the expression of Bcl-2 and Bcl-Xl in F9 teratocarcinoma stem cells [66]. In this study, the combination of the two agents resulted in a more effective and efficient induction of programmed cell death in SH-SY5Y cells.…”
Section: Ptnps and Ra Induce Ers And Apoptosismentioning
confidence: 57%
“…Similarly, the combination of silver nanoparticles and HDAC inhibitor increased the leakage of protease in human alveolar basal epithelial cells [63]. In addition, the combination of graphene oxide-silver nanoparticles and trichostatin A enhanced the leakage of intracellular protease in human ovarian cancer cells [65], and RA increased the leakage of LDH in F9 teratocarcinoma stem cells [66]. In this study, the rate of intracellular protease leakage into the cell medium was directly proportional to the cytotoxicity of PtNPs and RA against SH-SY5Y cells.…”
Section: Combination Of Ptnps and Ra Induces Lactate Dehydrogenase (Lmentioning
confidence: 97%
“…For example, PtNPs encapsulated within apoferritin exhibited high efficiency of cellular uptake and caused lower level of membrane damage. To avoid unnecessary impurities in nanoparticle preparation, Gurunathan and colleagues used various purified biomolecules such as saponin [16], quercetin [17], resveratrol [18], lycopene [19], R-phycoerythrin [20], and luteolin [21] during the synthesis of various nanoparticles, including silver, palladium, graphene, and gold.…”
Section: Introductionmentioning
confidence: 99%
“…The ER stress-induced disorder of Ca 2+ regulation after exposure to NMs, such as ZnO NPs (R. Chen et al, 2014), has been shown to initiate toxicological effects, including unfolded protein responses and apoptosis (Pirot, Eizirik, & Cardozo, 2006). Furthermore, NMs could also impair mitochondrial functions (Tsai et al, 2018) by decreasing the mitochondrial membrane potential (Gurunathan & Kim, 2018;Peng et al, 2018) and/or increasing the mitochondrial membrane permeability (Y. Yang, Xiao, et al, 2017), leading to an imbalance in mitochondria-mediated Ca 2+ homeostasis .…”
Section: [Ca 2+ ] I Alterationsmentioning
confidence: 99%